A 21st-century approach to school librarian evaluation - Owen, Patricia (Chicago, Ill. : American Association of School Librarians, 2012)
Provides school librarians an opportunity to engage in rigorous self-evaluation and to shape school administrator evaluations.
Includes bibliographical references.
Adult.
English.
Keywords: Instructional materials centers -- United states; Media programs (Education) -- United States -- Administration; School librarians -- United States -- Evaluation; School libraries -- United States -- Evaluation; Instructional materials centers -- United states; Instructional materials centers -- United states -- Administration; School librarians -- Evaluation; School libraries -- United States -- Evaluation